FACTORS ASSOCIATED WITH BREASTFEEDING SELF-EFFICACY IN THE IMMEDIATE PUERPERIUM IN A PUBLIC MATERNITY HOSPITAL - Siqueira, Laíse Sousa; Santos, Floriacy Stabnow; Santos, Romila Martins de Moura Stabnow; Santos, Livia Fernanda Siqueira; Santos, Leonardo Hunaldo dos; Pascoal, Livia Maia; Santos Neto, Marcelino (Cogitare Enfermagem, 2023)
Objective: to verify the association between sociodemographic variables, obstetric history, current pregnancy, and puerperium with breastfeeding self-efficacy. Method: cross-sectional study conducted in southwestern Maranhão, Brazil, between October 2020 and July 2021 with the participation of 240 postpartum women, using the Breastfeeding Self-Efficacy Scale - Short Form. Descriptive analysis, possible associations, simple and multiple logistic regression models were performed. Results: 83.3% had high breastfeeding self-efficacy, 46.7% were between 26 and 35 years old, 81.2% were married or in a stable union, 94.2% breastfed in the first hour of life, 37.9% received orientation on breastfeeding in the Primary Health Care Unit, and 84.2% offered only breast milk to the newborn in the maternity hospital. These factors were associated with high breastfeeding self-efficacy (p<0.05). Conclusion: The research contributed to guide health professionals to provide superior quality care to pregnant and postpartum women and lactating mothers, aiming to increase breastfeeding self-efficacy, identifying, among these women, those who need more support.